Penerapan Metode Webqual 4.0 Dalam Pengukuran Kualitas Website Awicoffee - Robet; Agus Maringan Siahaan; Satriya Miharja (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The measurement of Awicoffee’s website quality was conducted with the aim of enabling the website owner to develop aspects that have low value, so that they can continue to develop in line with the times. The data used for this research is the result of questionnaire distribution given to 100 respondents. Website quality measurement is carried out using the webqual 4.0 method with 3 aspects assessed, namely Usability, Information Quality, and Service Interaction Quality. The purpose of this research is to determine the satisfaction value of Awicoffee website users and to determine the most significant instrument in determining user satisfaction. Based on the research results, it was found that these three variables have an influence of 76.59% on user satisfaction, while 23.41% is influenced by variables that were not examined. Also, the variable that has the most significant impact on user satisfaction is Information Quality with a value of 5.97, whereas the Usability variable has a value of 3.42 and the Service Interaction Quality variable has a value of 3.30.